A randomised feasibility tolerability study of aminophylline for the prevention of preterm labour - Natasha Singh; Nishel Mohan Shah; Gavin Sooranna; Miriam Bourke; Angela Yulia; Cheryl Battersby; Rachel M. Tribe; Mark R. Johnson (BMC Pregnancy and Childbirth)
Abstract Background Progesterone is known to maintain uterine quiescence as pregnancy advances. Recently, its efficacy in preventing preterm birth has been questioned prompting a search for an alternative treatment option. Cyclic AMP has been shown invitro to act in synergy with progesterone to maintain uterine quiescence. Methods We undertook an open label randomised feasibility study to test the hypothesis that the addition of aminophylline to the standard of care (SoC) is acceptable and can be tolerated in pregnant women at high risk of spontaneous preterm labour (sPTL). Women at high risk of sPTL, who met the inclusion criteria were invited to participate and randomised to receive the SoC (progesterone alone, n = 33) or treatment with the SoC and aminophylline (n = 37). The main outcome measure was to assess the how many women at high-risk of sPTL tolerated and continued to take aminophylline. Data were analysed using Graphpad Prism 8.0c (Graphpad Software, San Diego, CA, USA). Results We found that of the addition of aminophylline was well tolerated in 30 of the 33 (91%) of women who continued in the combined arm, without any additional adverse maternal or fetal outcomes. 58% of eligible women agreed to participate in the study. The compliance rate was high at 99.42% +-0.82%. 67% of the women completed the post study questionnaire and all stated their willingness to take aminophylline if it were offered routinely for the prevention of sPTL. Conclusions The addition of aminophylline to the SoC is acceptable to women at high-risk of sPTL confirming that a randomised trial of aminophylline to reduce preterm delivery in women at high-risk of PTL is feasible. Trial registration Clinical trial gov NCT03152942. Date of full registration: 15/5/2017. https://clinicaltrials.gov/ct2/show/NCT03152942?cond=NCT03152942%26;draw=2%26;rank=1 .